MULTIPURPOSE GENE CONSERVATION IN QUERCUS-SUBER - A PORTUGUESE EXAMPLE - VARELA, M. C.; ERIKSSON, G. (SILVAE GENETICA, 1995)
Quereus suber, the native forest tree of highest economic value to Portugal is continuously declining. Creating good conditions for future evolution is the most important gene conservation objective for Quercus suber A simple breeding programme to improve the production of good cork is also included in the gene conservation objective. Gene conservation of species accompanying Quercus suber, or even dependent on Quercus suber, is a third objective. The suggested sampling of gene resource populations is mainly based on climatic, soil and management conditions of Quercus suber populations. Active selection of trees with good cork in small multiple populations growing over a broad array of site conditions is suggested to match the joint evolutionary and breeding objective in gene conservation. Management of large natural populations to create maximum habitat diversity is suggested to take care of the gene conservation of accompanying species. Knowledge of the genetic structure of Quercus suber and of gene now is urgently needed and ought to be given priority in genetic research.
AuthorAuthorThe following values have no corresponding Zotero field: pub-location: FINKENHOFSTRASSE 21, D-60322 FRANKFURT, GERMANY publisher: J D SAUERLANDERS VERLAG
Keywords: Cork oak; GENE CONSERVATION OBJECTIVES AND METHODS; Quercus suber; RESEARCH NEEDS